The Impact of The Covid-19 Pandemic on The Declining Trend of Hb0, Bcg, And Polio 1 Immunization Coverage in Makassar City - Yanti, Nur Fadylah; Utami Murti Pratiwi; Jelita Inayah Sari (Comprehensive Health Care, 2024)
Immunization comes from the word "immune," meaning resistant to a disease, but not necessarily resistant to other diseases. Immunization is the deliberate act of administering an antigen or bacteria from a pathogen to stimulate the immune system and induce immunity, resulting in only mild symptoms when exposed to certain diseases. COVID-19 is a type of coronavirus. The COVID19 pandemic, declared a pandemic by the WHO on March 11, 2020, has impacted health programs, particularly immunization services and surveillance of Vaccine-Preventable Diseases (VPDs). According to the Ministry of Health's 2020 data analysis, vaccination coverage decreased during the COVID-19 pandemic. This study aims to determine the impact of the COVID-19 pandemic on the declining trend of HB0, BCG, and Polio 1 immunization coverage in Makassar City. This research is an observational analytic study using a cross-sectional approach. The sample was taken using the total sampling method. Data analysis techniques were performed using the SPSS (Statistical Package for the Social Sciences) software. This study used data on the differences in coverage rates identified based on the periods of 2019, 2020, and 2021, and the division of health center areas in Makassar City. The conclusion of this study is that the COVID-19 pandemic has influenced the declining trend of HB0, BCG, and Polio 1 immunization coverage in Makassar City.